2014
DOI: 10.1109/thms.2013.2294636
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Air Versus Ground Vehicle Decisions for Interfacility Medical Transport Using Historical Data

Abstract: Patients undergoing interfacility transfers are at potentially greater risk of adverse or critical events than those in hospital, and efficient transfers play a significant role in reducing mortality and morbidity. Medical dispatchers rely on accurate estimations of transfer time in determining the most appropriate method of transportation, often either a helicopter and/or land ambulance, in situations that are characterized by high time pressure and uncertainty. In this paper, we propose the design of a datad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Our previous work has shown that dispatchers tend to underestimate the time required to transfer patients (Giang, Donmez, Fatahi, Ahghari, & MacDonald, 2014). The underestimation also appeared to be greater for transfers made by air than those made by land, a bias that may have consequences when dispatchers need to choose the mode of transportation for completing an interfacility transfer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous work has shown that dispatchers tend to underestimate the time required to transfer patients (Giang, Donmez, Fatahi, Ahghari, & MacDonald, 2014). The underestimation also appeared to be greater for transfers made by air than those made by land, a bias that may have consequences when dispatchers need to choose the mode of transportation for completing an interfacility transfer.…”
Section: Introductionmentioning
confidence: 95%
“…The prototype decision support tool (Giang et al, 2014) was designed to support interfacility transfers and produces estimates of time to definitive care using historical transfer time data provided by Ornge. Users are required to input information about the requested transfer, including sending and receiving facilities, the 2015 International Symposium on Human Factors and Ergonomics in Health Care: Improving the Outcomes vehicles to be used (often a land and air vehicle for comparison), the Ornge base where the vehicles are located, and any landing sites required for the aircraft.…”
Section: Decision Support Tool For Travel Time Estimatesmentioning
confidence: 99%
“…19 Fleischman et al built and validated a model of ambulance arrival times using historical data from Multnomah County, Oregon (USA). 2 The models presented in this study can be incorporated in similar aids and models to improve the accuracy of estimated times. However, presence of wet weather (any transfer that occurred during a day with more than 0.01 inches of precipitation) and patient-related conditions were not significant predictors.…”
Section: Decision Support and Predicting Future Transfer Timesmentioning
confidence: 99%
“…2,12 In general, the lower resolution is expected to generate more conservative effects of precipitation. In particular, five weather stations located in five different cities covered most of the sending and receiving facility locations and were used for precipitation information.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation